Hospital Digitalization Effects on Patient Outcomes Mediated by Usability Pathways - Rusli, Laurencya Stephanie; Prasetianto, Aditia; Lina, Lina (Jurnal Minds: Manajemen Ide dan Inspirasi, 2026)
This study examines how administrative and patient service digitization influence patient satisfaction and loyalty in hospital settings. It advances digital health literature by demonstrating that hospital digitalization effects on patient outcomes are mediated by usability pathways rather than direct technological deployment, while also revealing the contingent role of digital literacy across service domains. Using a PLS-SEM approach with a sample of 196 patients, the findings indicate that digitalization does not directly enhance satisfaction or loyalty but operates through perceived ease of use, whereas perceived usefulness remains non-influential. Digital literacy strengthens the impact of administrative digitization on satisfaction but weakens the effect of patient service digitization. Satisfaction emerges as the primary driver of patient loyalty. These findings imply that hospital digital transformation strategies should prioritize usability optimization and tailor digital services to patient capability levels.